Flow Characteristics and Pipeline Stability in Slope-Confined Submarine Canyons - Dejun Wang; Jun Huang; Xianhong Feng; Huaqing Liu; Yuqi Dong; Zhimeng Gong; Zhihui Jiao; Yunfei Teng; Zhichao Shen; Yan Qu (Journal of Marine Science and Engineering, 2026)
Numerical simulations are conducted to investigate the near-bed flow behaviors of submarine canyons with periodic ridge-valley topography on continental slopes. In the numerical simulation, two topographic parameters are defined: α represents the basal slope angle of the continental slope, and β denotes the side slope angle of the submarine canyon. The topographic modulation of these two parameters on near-bed flow velocity and pipeline on-bottom stability is explored. The results show that the ribbed slope exerts two distinct modulation mechanisms on near-bed flow fields, which are governed by the relative angle between incoming flow and ridge-valley structures. When the flow is perpendicular to the canyon axis (θ = 0°), local topographic contraction and expansion accelerate flow over ridge crests and reduce near-bed velocity in valleys as β increases. In contrast, when the flow is parallel to the canyon (θ = 90°), lateral confinement by bilateral ridges forms a topographic channel, leading to persistent flow acceleration throughout the entire valley area. Moreover, such directional velocity differences substantially alter the on-bottom stability of pipelines deployed within the canyon. Two pipe-soil interaction models are employed in the stability analysis: the Verley-Lund model for a flat clayey seabed and the Slope-Silt model for a sloping silty seabed. The sensitivity of their predictions to soil undrained shear strength is further evaluated.

Bifidobacterium longum engineered with artificial enzymes alleviates high-altitude colitis via inhibition of GPD2-dependent ferroptosis - WenQiang Yuan; Fang Yan; LiuChan Yang; YunHan Yang; Chen Chen; ShiMin Wu; DeJun Cui (Protoplasma, 2026)

Mechanistic insights into electric-field-induced ice suppression and ion migration in ice-channel-confined NaClO4 electrolyte - Zhenyu Zhang; Dejun Xiong; Zizhen Yan; Yang Guo; Heng Zhang; Shiling Yuan (Chemical Engineering Journal, 2026)

Precise mapping of high-temperature adult-plant stripe rust resistance gene Yr52 in wheat - Mingjie Xiang; Yibo Zhang; Shuaiwei Cao; Jiangna Han; Haohao Yan; Chenfang Wu; Jiale Li; Xunying Yuan; Xiangrui Cheng; Shuqing Yang; Zhuang Li; Xiaoting Wang; et al. (Theoretical and Applied Genetics, 2026)

Performance and Mechanism of Photo-electrocatalytic Inactivation of Chlorella vulgaris Under Sunlight Irradiation - Xueming Zhang; Dejun Lian; Limei Xu; Lei Ma; Yin Su; Zhen Yan (Water Conservation Science and Engineering, 2026)

Study on the degradation performance and toxicity reduction mechanism of electroplating wash wastewater by a hydrolysis–acidification–MPR synergistic system - Weiqing Jiang; Jinhao Pu; Fan Wang; Jiulin Yan; Qing Yang; Siwen Yang; Dejun Bian (Journal of Environmental Management, 2026)

Supercritical CO2-assisted pressure homogenization for exfoliating natural graphite toward high-performance graphene cathodes in aluminum-ion batteries - Yue Wu; Jianmin Feng; Li Wang; Jiacheng Qiu; Xuan Song; Xuwang Fu; Ziqi Luo; Jiahan Ma; Xiaoyu Yu; Lei Dong; Yan Han; Conglai Long; et al. (Chemical Engineering Journal, 2025)

Effects of polysaccharides on protein in vitro digestion and rheological properties under simulated elderly gastric conditions - Jiaxin Chang; Yan Zeng; Huangqiao Tao; Dejun Hu; Wei Zhao; Suilou Wang; Chongjiang Cao (Food Chemistry, 2025)

Genotyping by target sequencing (GBTS)-based genetic mapping uncovers synergistic interactions for stripe rust resistance in wheat cultivar Flanders - Lei Liu; Jinyu Han; Dandan Zhang; Yuqing Li; Chuanliang Zhang; Shengjie Liu; Ziyi Yan; Weijun Zheng; Chunlian Li; Qingdong Zeng; Zhensheng Kang; Dejun Han; et al. (Theoretical and Applied Genetics, 2025)

Chlorophenols suppress gametogenesis by disrupting sex hormone signaling through DNA methylation in zebrafish - Rongjian Liu; Dongqiong Wei; Xuan Ma; Jiamin Shi; Yan Hu; Samra; Cong Yuan; Yongmei Qi; Dejun Huang (Environmental Pollution, 2025)

N/O co-doped hollow sphere-like hard carbon with hierarchical pores for fast and high-capacity Na+/Li+ storage - Chenchen Bai; Bingjun Li; Chang Shu; Wenjie Chen; Yan Han; Dejun Li (Chemical Engineering Journal, 2025)

Analysis of pollutant removal regularities and sludge-film co-existence characteristics in OAO micro-pressure internal circulation composite biological treatment process - Fan Wang; Hua Kang; Shengshu Ai; Fangyuan Zhang; Qin Cui; Jiulin Yan; Dejun Bian (Journal of Water Process Engineering, 2025)

Epidemiological and genomic analysis revealed the significant role of flies in dissemination of carbapenem-resistant Enterobacteriaceae (CRE) in China - Hongwei Zhou; Hanyu Wang; Kaichao Chen; Miaomiao Xie; Zelin Yan; Yanyan Zhang; Yuchen Wu; Dejun Liu; Juan Wang; Ning Dong; Chang Cai; Yongning Wu; et al. (Journal of Hazardous Materials, 2024)

A clearance control and interference repair method for ship rib plate assembly based on reverse engineering - Yifan He; Yu Chen; Xiaofeng Zou; Dazhi Zhou; Jinfeng Liu; Dejun Yan (Ocean Engineering, 2024)

A polysaccharide NAP-3 from Naematelia aurantialba: Structural characterization and adjunctive hypoglycemic activity - Lu Sun; Jiang Jiang; Tao Jing; Dejun Hu; Jie Zhu; Yan Zeng; Yalun Pang; Dechun Huang; Shujie Cheng; Chongjiang Cao (Carbohydrate Polymers, 2023)

Molecular characterization and validation of adult-plant stripe rust resistance gene Yr86 in Chinese wheat cultivar Zhongmai 895 - Zhanwang Zhu; Qiang Cao; Dejun Han; Jianhui Wu; Ling Wu; Jingyang Tong; Xiaowan Xu; Jun Yan; Yong Zhang; Kaijie Xu; Fengju Wang; Yachao Dong; et al. (Theoretical and Applied Genetics, 2023)

De novo transcriptome analysis of Fraxinus velutina Torr in response to NaCl stress - Liping Yan; Cuilan Liu; Yinhua Wang; Kaifang Wang; Fei Ren; Junxiu Yao; Dejun Wu (Tree Genetics & Genomes, 2019)

Inhibitory action of chamaejasmin A against human HEP-2 epithelial cells: effect on tubulin protein - Yan Zhao; Fenglian Wu; Yu Wang; Shengwu Chen; Guojun Han; Ming Liu; Dejun Jin (Molecular Biology Reports, 2012)

Nocodazole increases the ERK activity to enhance MKP-1 expression which inhibits p38 activation induced by TNF-α - Xiangrui Guo; Xueying Zhang; Yajing Li; Yuanyuan Guo; Jing Wang; Yan Li; Beifen Shen; Dejun Sun; Jiyan Zhang (Molecular and Cellular Biochemistry, 2012)

Influence of fertilizers on nitrogen mineralization and utilization in the rhizosphere of wheat - Ling Yuan; Dejun J. Bao; Yan Jin; Yuhong H. Yang; Jianguo G. Huang (Plant and Soil, 2011)